Peningkatan Kesadaran Lingkungan Dalam Pengelolaan Lingkungan Biota Laut Masyarakat Pesisir Di Desa Wiring Tasi Kecamatan Suppa - Dahniar Daud; Chaerunnisa Rumianti; Djamilah Saleh; A. Tenriola; Erniwati Madya; Muhammad Irfai Sohilauw (Institut Teknologi dan Bisnis Semarang, 2024)
This activity aims to increase environmental awareness in environmental management of marine biota in coastal communities in Wiring Tasi village, Suppa District. This activity was carried out in collaboration with TSJL PT PLN Makassar region and STIEM Bongaya Makassar and took place on 4 and 5 November 2024. This activity was attended by 15 people from the coastal community of Wiring Tasi village, Suppa District, Pinrang. The activity method is carried out by presenting the material and continuing with discussion activities. The target to be achieved in community service activities for lecturers and students of the Accounting and Management Study Program in Coastal Communities in Suppa is: Increasing understanding and knowledge of the community regarding the concept of ecotourism development in improving community welfare. The results of this activity provide positive benefits for the community, educate and share knowledge for mutual progress. The target of this activity is for coastal communities to support economic growth by preserving the environment, with the hope that ecotourism can increase tourist visits in the area which can contribute to improving the welfare of the community. MSMEs can grow and develop, contribute more to the community, and create new jobs.